Site-dependent nuclear dynamics in core-excited butadiene. Issue 47 (24th November 2022) - Oghbaiee, Shabnam; Gisselbrecht, Mathieu; Walsh, Noelle; Oostenrijk, Bart; Laksman, Joakim; Månsson, Erik P.; Sankari, Anna; Eland, John H. D.; Sorensen, Stacey L.
Abstract : Auger decay from terminal carbon (left) leads to dynamic processes while Auger decay from the central carbon site in butadiene does not. Abstract : Symmetry breaking and competition between electronic decay and nuclear dynamics are major factors determining whether the memory of the initial core-hole localisation in a molecule is retained long enough to affect fragmentation. We investigate the fate of core holes localised at different sites in the free 1, 3 trans butadiene molecule by using synchrotron radiation to selectively excite core electrons from different C 1s sites to π* orbitals. Fragmentation involving bonds localised at the site of the core hole provides clear evidence for preferential bond breaking for a core hole located at the terminal carbon site, while the signature of localisation is weak for a vacancy on the central carbon site. The origin of this difference is attributed to out-of-plane vibrations, and statistical evaporation of protons for vacancies located at the central carbon sites.